Sindrom Makan Malam, Konsumsi Ultra-processed Foods, dan Aktivitas Fisik sebagai Faktor Risiko Gizi Lebih pada Mahasiswa Fakultas Ilmu Kesehatan UPN “Veteran” Jakarta: Night Eating Syndrome, Ultra-processed Foods Consumption, and Physical Activity as Risk Factors for Overnutrition in Students of Faculty of Health Science UPN “Veteran” Jakarta - Hanifa, Raishi Amatullah; Arini, Firlia Ayu; Wahyuningsih, Utami (Amerta Nutrition, 2024)
Background: Overnutrition among university students is a pressing concern, disrupting academic productivity and increasing the risk of metabolic diseases at a young age. According to RISKESDAS (2018), the prevalence of overweight/obesity among early adulthood populations reached 36%. Dietary patterns, unhealthy lifestyles, and night eating syndrome (NES) may contribute to overnutrition cases in university students. Objectives: This study aimed to investigate the association between night eating syndrome, ultra-processed food consumption, physical activity, and overnutrition among students at the Faculty of Health Science, UPN "Veteran" Jakarta. Methods: This analytical case-control study included 94 participants (47 case and 47 control), aged 19-24 years, from UPN “Veteran” Jakarta. Inclusion criteria comprised students with Body Mass Index (BMI) > 25 (case group) and BMI 18.5-25 (control group). Data collection employed anthropometric measurements, individual assessment using Night Eating Questionnaire (NEQ), Food Frequency Questionnaire (FFQ), and International Physical Activity Questionnaire (IPAQ). Bivariate analysis utilized Chi-square tests. Results: Results indicated a significant association between night eating syndrome and overnutrition (p-value=0.004, OR=5.214). No significant associations were observed between ultra-processed food (UPF) consumption (p-value=0.409) or physical activity (p-value=0.149) and overnutrition. Conclusions: This study concluded that night eating syndrome significantly predicts overnutrition incidence. Conversely, UPF consumption and physical activity demonstrated no significant associations with overnutrition.